Non-cancer-specific survival in patients with primary central nervous system lymphoma: A multi-center cohort study - Chi, Kaiyi; Zhou, Ruoyun; Luo, Zehao; Zhao, Hongjun; Jiang, Yanting; He, Baixin; Li, Yemin; Chen, Dongting; Feng, Manting; Liang, Yinglan; Yang, Wenting; Liu, Ruisi; et al. (Frontiers in Oncology, 2023)
Objective: To evaluate the non-cancer-specific death risk and identify the risk factors affecting the non-cancer-specific survival (NCSS) in patients with primary central nervous system lymphoma (PCNSL). Methods: This multi-center cohort study included 2497 patients with PCNSL in the Surveillance, Epidemiology and End Results (SEER) database from 2007 to 2016, with a mean follow-up of 4.54 years. The non-cancer-specific death risk in patients with PCNSL and primary central nervous system diffuse large B-cell lymphoma (PCNS-DLBCL) was evaluated using the proportion of deaths, standardized mortality ratios (SMRs), and absolute excess risk (AERs). Univariate and multivariate competing risk regression models were utilized to identify risk factors of NCSS. Results: PCNSL was the most frequent cause of death in PCNSL patients (75.03%); non-cancer-specific causes make up a non-negligible portion of death (20.61%). Compared with the general population, PCNSL patients had higher risks of death from cardiovascular disease (CVD) (SMR, 2.55; AER, 77.29), Alzheimer’s (SMR, 2.71; AER, 8.79), respiratory disease (SMR, 2.12; AER, 15.63) and other non-cancer-specific diseases (SMR, 4.12; AER, 83.12). Male, black race, earlier year of diagnosis (2007-2011), being unmarried, and a lack of chemotherapy were risk factors for NCSS in patients with PCNSL and PCNS-DLBCL (all P < 0.05). Conclusion: Non-cancer-specific causes were important competing causes of death in PCNSL patients. More attention is recommended on non-cancer-specific causes of death in the management of PCNSL patients.